KONTEKSTUALISASI PEMAHAMAN HADIS - Nawir Yuslem (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2010)
Abstract: Contextualization of Comprehending Prophetic Traditions (hadîth). Prophetic traditions (hadîth) which is considered as the second source of guidance for the Muslim’s way of life, also functions as explanatory injunction of the messages inherent in the Qur’an which render infinite or global meanings. The author argues that due to its detailed and operative character in explaining the meaning of the Qur’an so that it can be applied in the real life in accordance with time and space, hadîth has often been misunderstood without considering the context of the ever-developing life. In the present essay, the writer attempts to analyze contextual theory as an alternative theory in semantics that can be implemented in understanding the prophetic tradition. Kata Kunci: matan, dalâlah, pemahaman hadis